(untitled) (Bangladesh Journal of Otorhinolaryngology, 2020)
Adeno- tonsillitis is the commonest disease of the children and the adolescent among the ENT diseases all over the world. Adeno- tonsillectomy is the surgery mostly performed. Conventional curettage method is usually done by most of the surgeons. Residual adenoid tissue remains following this blind approach even with skill hands which is responsible for most of the recurrences. Whatever the device or instrument used in mirror guided surgery chance of recurrence is almost none. Moreover complication is also negligible. 137 cases were studied using this procedure showed very effective result with few complications. Bangladesh J Otorhinolaryngol; April 2016; 22(1): 31-35